âAKU KAPAN SIALâ (AKADEMI KHUSUS KILAT ANAK PANTI SOSIAL) - Candra, Agus; H, Hariyani; H., Herla; Ritno, Muhammad Dezar; Fatlullah, Uwu Holifa Ana (Program Kreativitas Mahasiswa - Pengabdian Kepada Masyarakat, 2013)
According to data from 2008-2012 recorded there are 945 students PSBR have and are getting guidance to the percentage of success is 60.63% independent/ working and 39.37% status is not clear. The purpose of this activity is implementation of a waste management training to be creative, innovative and economy products like sofa from plastic bottles, plus-pack (stationery box), make growing media from waste paper and manufacture of plastic fruit crops such as citrus fruit plants, peppers and eggplant. In addition, the workshop was also held bussines workshop to finalize their business plan opportunities that they would do after graduating from social institutions.